Pilot testing the Engaging Generations (eGen) Program to address social well-being among lower-income older adults - Tsotsoros, Cindy E.; Pascuzzi, Emma; Brasher, Melanie; Souza, Kristin; Leedahl, Skye N. (Frontiers in Public Health, 2024)
Introduction: Throughout the COVID-19 pandemic, the need to address digital inclusion and social well-being for older adults was particularly apparent for those from disadvantaged communities. This pilot program provided access to technology and intergenerational mentorship to older adult participants interested in receiving and learning how to utilize an iPad. Pre/post-changes were examined for social well-being in the areas of quality of life, social isolation, and loneliness. Methods: This study conducted pre- and post-surveys with older participants (n=145) from five disadvantaged communities in the United States utilizing standardized measures. One-on-one interviews were conducted post-program (n=98) to examine participants’ perceptions of the program and evaluate its impact on social measures. Results: The study sample included older adults (Mean age=72.3) who were mostly lower income (82.3%) and self-reported as Black (13.6%), Hispanic (21.7%), and White (56.5%). Significant differences were identified in participant pre/post-survey scores for social isolation, loneliness, and a global measure of quality of life. Qualitative analyses suggest improvements in various aspects of social well-being. Themes showed that participants believed the program contributed to 1) enhanced mood and mental health, 2) improved quality of life, 3) sense of purpose and feelings of being less alone, 4) ability to use video calling to connect with others; and 5) ability to more freely use email, texting, and messaging to communicate with others. Discussion: This research demonstrates that this pilot program seemed to contribute to reduced social isolation and loneliness for participants, and participants stated more positive social well-being following program participation. However, future research with larger samples is needed to expand upon these findings. Future studies will examine the pathways between technology improvements and social well-being and examine group differences.